Comparative Toxicity of Four Detergents on a Prawn Metapenaeus dobsoni (Miers) - B., Sakunthala; H., Shanmukhappa; B., Neelakantan (Fishery Technology, 2025)
The toxicity bioassay experiment was conducted using four detergents, namely, linear alkylbenzene sulfonate (LAS), branched alkylbenzene sulfonate (BAS), alfa olefin sulfonate (AOS) and sodium sulfonate (SS.) on Metapenaeus dobsoni juveniles. The results indicated that, LAS was most toxic and AOS the least and were in the order: LAS>SS. >BAS>AOS. The LCN, LC50 and LC84 concentrations for all the detergents were calculated for 24, 48, 72 and 96 hours. The 95 % confidence limits for LC50 and slopes were also calculated by probit analysis.